Reciprocal teaching strategies at work [videorecording] improving reading comprehension, grades 2-6 - Oczkus, Lori D. (International Reading Association, 2005)
This presentation shows how to improve students' reading comprehension by implementing reciprocal teaching in the classroom. Includes sample lessons, in-class observational footage, and testimonials from teachers who have used the program.